EFFECT OF WORK-LIFE BALANCE AND WORK ENVIRONMENT ON EMPLOYEE SATISFACTION (CASE STUDY IN A MANUFACTURING COMPANY IN THE CITY OF BANDUNG) - Irfan Nur Iryandi; Farid Riadi (Jurnal Computech & Bisnis (e-Journal), 2022)
This research aims to know the effect of Work-Life Balance and Work Environment on Employee Job Satisfaction in one of the manufacturing companies in the city of Bandung. Moreover, this research analyzes the factor that has the most dominant influence between Work-Life Balance and Work Environment on Employee Job Satisfaction in a manufacturing company in the city of Bandung, which is the object of research for as many as 60 employees using a questionnaire.Based on path analysis research, the work-life balance and work environment variables on job satisfaction in one of the manufacturing companies in the city of Bandung are declared valid. As for the conclusion, suggestions concerning the research results are paying attention to Work-Life Balance and Work Environment to increase Employee Job Satisfaction.Key Words: Work-Life Balance, Work Environment, Employee Job Satisfaction